PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA EKSEKUTIF PUBLIK DENGAN MORAL HAZARD SEBAGAI VARIABEL PEMODERASI (Studi Kasus di Pemerintah Daerah Kabupaten Sumenep) - Siti Musyarofah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
Bottom up system in budgeting process is more adopted for this time. But effectiveness of this system in increasing managerial performance is debatable because of individual motivation that reflected hazard moral. This research tries to examine the effect of budget participation to managerial performance with moral hazard as moderating variable. This research is a case study in Sumenep – Madura (East Java), with respondents are public executive at SKPD (Satuan Kerja Perangkat Daerah) whom included in budget team. There were 70 respondents who  participated in this research. The hypotheses was examined with multiple regression in interaction model with absolute difference. The results show that high budget participation will increase managerial performance if lower hazard moral is not supported with alpha 5%. Although interaction model is statistically significant, but interaction coefficient is negative at -4,492, this caused hypothesis is reject